Phytochemical profile and antioxidant potential of leaf and bark extracts of Cassine glauca (Rottb.) Kuntze - Dhanasekaran, K.; Ashok, Kishore Kumar; Palanisamy, K.; Subramaniam, P.; Balakrishnan, V. (Journal of Phytology, 2025)
In the present study the phytochemical composition and antioxidant prospective of Cassine glauca leaf and bark extracts. Leaf and bark of C. glauca were extracted by methanol and chloroform through Soxhlet extraction. The extracts were analyzed for qualitative and quantitative phytochemical constituents, including phenolics, flavonoids, tannins, and other bioactive compounds. Antioxidant activity was determined through five different methods such as DPPH radical scavenging, reducing power, assay of molybdenum, hydrogen peroxide (H2O2) scavenging, and nitric oxide scavenging assays. Phytochemical analysis revealed that methanol extracts from both leaf and bark were more effective than chloroform, showing higher concentrations of phenolics, tannins and flavonoids. The leaf extract had a total phenol content of 47.458 mg GAE/g, tannins at 45.298 mg RE/g. and a flavonoid content of 160.106 mg TAE/g, and the bark extract showed lower but notable levels of these compounds. The leaf extract showed greater antioxidant activity when compared with bark extract in all experiments, includes DPPH radical scavenging activity, molybdenum assay, reducing power activity, nitric oxide scavenging activity and H2O2 scavenging activities. Methanol extracts of C. glauca leaf and bark exhibited significant antioxidant properties, with the leaf extract showed greater efficacy. The present study highlights a prospective source of C. glauca as a potential resource of natural antioxidants and suggests additional exploration of its therapeutic benefits in oxidative stress-related disorders. The results emphasize the effectiveness of methanol as a solvent for extracting potential bioactive compounds from C. glauca.